The Effect of Store Atmosphere on Impulse Buying Mediating Positive Emotion: Case Study of Guardian’s Customers at Olympic Garden Mall) - Ova Nia Amalia; Marsudi Marsudi; Sri Nastiti Andharini (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
The purpose of this study was to describe the role of positive emotion in mediating the effect of store atmosphere on impulse buying at the Guardian Store at Mall Olympic Garden in Malang. The population in this study were the Guardian visitors at Mall Olympic Garden. The sample in this study was 120 respondents using purposive sampling. The analysis technique used is the scale range, path analysis, and single test. The results showed that store atmosphere has a positive and significant influence on impulse buying, store atmosphere has a positive and significant influence on positive emotion, positive emotion has a positive and significant effect on impulse buying and positive emotion can be a mediating variable between the influence of store atmosphere on impulse buying